Challenges of Gender Stereotypes in Women's International Leadership Careers: Literature Review - Bayu Suryo Putro; Didin Hikmah Perkasa; Ahmad Badawi Saluy (Dinasti Review, 2025)
This literature review examines the challenges that gender stereotypes pose to women's advancement in international leadership roles. The review identifies obstacles such as limited access to top positions, gender pay gaps, and societal attitudes that favor men. Gender stereotypes contribute to conscious and unconscious biases, discriminatory practices, unequal opportunities, and the